Möglichkeiten und Grenzen der interkulturellen Sprachvermittlung - Pfeifer, Waldemar (Glottodidactica, 2000)
This article is a basic discussion on the problems of intercultural learning in foreign language teaching. Starting from the statement that the concept of intercultural education has become one of the most widely discussed and most popular topics in the disciplines of arts and social sciences the author examines in the first part of the article the origin of intercultural orientation and discusses the main Landeskunde-theories and the most important cultural contents in the practice of foreign language teaching. In the second part of the article the dangers of overusing of intercultural objectives are reflected and future perspectives for methods of intercultural foreign language teaching are suggeste